Thinking critically - John Chaffee (New Delhi Cengage Learning Pvt. Ltd., 2019)
Become a more sophisticated thinker with THINKING CRITICALLY, which teaches you a surefire process for developing the thinking abilities you need for academic and career success. First, you'll build your confidence by learning and practicing basic skills related to your personal experiences. Next, you'll progress to the types of reasoning skills required for abstract contexts -- such as your academic courses. Activities and writing assignments invite your active participation and prompt you and your peers to critically examine each other's thinking. Thought-provoking and current readings from a wide variety of thinkers engage you in thinking about complex issues from different perspectives. Along the way, monitor your own progress as a critical thinker with self-assessment activities.
Keywords: Critical Thinking